Advancements, criticisms and pending challenges of educational policy during the presidency of Rafael Correa Ecuador 2007-2017 - Guayasamin Mogrovejo, Mateo Nicolás (IE Revista de Investigación Educativa de la REDIECH, 2017)
The following work inquiries about the political advancements and setbacks of the Ecuadorian education system during Rafael Correa’s government. The method for analysis comes from categories and concepts of public education policies. This analysis is expected to elaborate on the main indicators that describe all achievements, as well as critiques of how his policies have impacted education during his time in power. At the end we will see which were the main challenges of the Ecuadorian educational system in the context of political transition, economic recession and neo-capitalist globalization.